Patterns of lymphatic drainage after axillary node dissection impact arm lymphoedema severity: A review of animal and clinical imaging studies. (December 2018) - Suami, Hiroo; Koelmeyer, Louise; Mackie, Helen; Boyages, John
Abstract: Upper extremity lymphoedema after axillary node dissection is an iatrogenic disease particularly associated with treatment for breast or skin cancer. Anatomical studies and lymphangiography in healthy subjects identified that axillary node dissection removes a segment of the lymphatic drainage pathway running from the upper limb to the sub-clavicular vein, creating a surgical break. It is reasonable to infer that different patterns of lymphatic drainage may occur in the upper limb following surgery and contribute to the various presentations of lymphoedema from none to severe. Firstly, we reviewed animal imaging studies that investigated the repair of lymphatic drainage pathways from the limb after lymph node dissection. Secondly, we examined clinical imaging studies of lymphatic drainage pathways after axillary node dissection, including lymphangiography, lymphoscintigraphy and indocyanine green fluorescence lymphography. Finally, based on the gathered data, we devised a set of general principles for the restoration of lymphatic pathways after surgery. Lymphoscintigraphy shows that restoration of the original lymphatic pathway to the axilla after its initial disruption by nodal dissection was not uncommon and may prevent lymphoedema. We found that regenerated lymphatic vessels and dermal backflow (the reflux of lymph to the skin) contributed to either restoration of the original pathway or rerouting of the lymphatic pathway to other regional nodes. Variation in the lymphatic drainage pathway and the mechanisms of fluid drainage itself are the foundation of new lymphatic drainage patterns considered to be significant in determining the severity with which lymphoedema develops. Highlights: Axillary dissection removes a segment of the normal lymphatic drainage pathway. Regeneration of lymphatics to the axilla is common after an axillary dissection. Dermal backflow contributes to the formation of new collateral pathways. Different drainage patterns correlate with the variable presentation of lymphoedema.